The arts of fighting and of scholastic dispute: two types of duels at the end of the Middle Ages and during the Renaissance - Pierre-Henry Bas (Bern Open Publishing, 2023)
Fencing and the art of combat in general can bring you to think of an argument, a serious conversation between two individuals or two groups. Conversely, intellectual disputes and discursive exchanges can be compared to actual duels with the difference that questions, answers, and reasoning replace gestures, defences, and attacks. This rather simplistic vision deserves to be questioned in regard to the medieval and Renaissance periods, in particular from the written productions resulting from the theorisation and the inscription of these two forms of interaction: the scholastic dispute and the art of fencing. This article aims to make the link between the mechanism of the scholastic dispute, which has existed since the Middle Ages and which persists in the Renaissance, and the world of the art of medieval and early modern combat, which is materialised through the treatises of fencing and wrestling written by educated masters-at-arms as well as the practice of public fencing competitions.